The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.6004/jnccn.2018.7187
|View full text |Cite
|
Sign up to set email alerts
|

QIM19-136: Developing an Ideal CAR-T Cell Therapy Patient Experience Through Human-Centered Design and Innovation

Abstract: Background: The patient/caregiver experience during CAR-T therapy is stressful, overwhelming, terrifying, and often a patient’s last treatment option. The Mayo Clinic Robert D. and Patricia E. Kern Center for the Science of Health Care Delivery Innovation and Design team has worked with the CAR-T therapy clinical team to develop a patient experience that provides patients with a sense of caring, supportive environment, timely knowledge, and realistic expectations. Using a human-centered design approach, the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Little is known about patient priorities and needs after CAR-T therapy, but the current literature underscores the importance of appropriate information. By interviewing patients, Matthews et al found that most felt unprepared for the emotional aspects of CAR-T therapy nor were they prepared for the intensity of the toxicities (Matthews et al 2019). The importance of addressing issues, such as clear information on the treatment trajectory (Bamigbola et al 2021), financial toxicity, and the importance of family members and other caregivers, has also been described .…”
Section: Key Pointsmentioning
confidence: 99%
“…Little is known about patient priorities and needs after CAR-T therapy, but the current literature underscores the importance of appropriate information. By interviewing patients, Matthews et al found that most felt unprepared for the emotional aspects of CAR-T therapy nor were they prepared for the intensity of the toxicities (Matthews et al 2019). The importance of addressing issues, such as clear information on the treatment trajectory (Bamigbola et al 2021), financial toxicity, and the importance of family members and other caregivers, has also been described .…”
Section: Key Pointsmentioning
confidence: 99%
“…Centers have implemented a multidisciplinary evaluation from geriatricians, physical and occupational therapy, social workers, and dieticians before stem cell transplants to not only select appropriate patients but act on modifiable risk factors [54]. Other centers have implemented remote monitoring, utilizing the digital platform for patient education to identify barriers to access and study patient-reported outcomes [55]. For improved access, it is critical for a holistic approach for patients undergoing CAR T cell therapy.…”
Section: Financial and Social Supportmentioning
confidence: 99%
“…Little is known about patient priorities and needs after CAR-T therapy, but the current literature underscores the importance of appropriate information. By interviewing patients, Matthews et al found that most felt unprepared for the emotional aspects of CAR-T therapy nor were they prepared for the intensity of the toxicities (Matthews et al 2019). The importance of addressing issues, such as clear information on the treatment trajectory (Bamigbola et al 2021), financial toxicity, and the importance of family members and other caregivers, has also been described (Foster et al 2020).…”
mentioning
confidence: 99%